The Enterprise2 Stent for Endovascular Treatment of Intracranial Aneurysms: Short-Term Results From a Single Center Experience - Chen, Linhui; Zheng, Chaobo; Wu, Jiong; Gong, Jie; Gao, Yuhai; Wan, Shu (Frontiers in Neurology, 2020)
Background Self-expanding devices, such as the Enterprise VRD (EP-VRD) have widely used for stent-assisted coiling treatment in wided-necked aneuryms while some thromboembolic complications were reported due to its incomplete stent apposition (ISA). We report our experiences on the novel Enterprise2 (EP-VRD2) stent in vivo in the treatment of intracranial and cranial cervical junction aneurysms. Methods Twenty-five consecutive patients with intracranial or cranial cervical junction aneurysms were treated with EP-VRD2 stents retrospectively collected in our institution. We use the 'jailing' technique in all cases and deployed the stent by using pushing over the outer curve technique. The 3- or 6-month follow-up was done regularly by DSA. Results Twenty-five EP-VRD2 stents were implanted to treat 21 aneurysms at the siphon segment of internal carotid artery (ICA), 1 at the petrous segment, 2 at the cervical segment, 1 at the verteral artery with 5 accompanied with stenosis. Two patients had kinking during the procedure and were solved by microwire or microcatheter massaging. 4 patients with a larger arc angle and a smaller radius of the parent vessel was detected ISA. No patient underwent the ischemic event after the operation. 23 of 25 patients were evaluated after 3- or 6-month by DSA, 22 showed complete occlusion (RROC1), one slight re-stenosis in the follow-up within those five patients with stenosis. A length of 23mm seemed associated with ISA (p<0.01). Conclusion The EP-VRD2 performed well in our small patient series; however, ISA could still occur with a sharp angle of the parent vessel.